IMPLEMENTATION OF E-BUDDY IN THE ADMINISTRATIVE PROCESS IN PERMISAN VILLAGE, JABON - Nugraeni, Annisa Cahyaning; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study discusses the implementation of the E-Buddy application in the administrative process in Permisan Village, Jabon District. E-Buddy is a digital innovation for managing correspondence as part of e-Government. Method: The research method uses a qualitative descriptive approach with interviews, observation, and documentation. The analysis is based on George C. Edward III's policy implementation theory which includes communication, resources, disposition, and bureaucratic structure. Result: The results show that communication and resources are adequate. However, disposition is still not optimal due to manual procedures, as village heads have not actively used the E-Buddy application. The bureaucratic structure is in accordance with standard operating procedures (SOPs), but further commitment is needed. Overall, E-Buddy has had a positive impact on the effectiveness of village administration, although implementation challenges remain. Novelty: The novelty of this research lies in its focus on the implementation of the E-Buddy application in Permisan Village which has never been studied before, as well as the in-depth use of George C. Edward III's policy implementation theory and the presentation of periodic data.